2022
DOI: 10.29313/jrmb.v1i2.543
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kecerdasan Emosional dan Disiplin Kerja terhadap Komitmen Karyawan pada PT. X

Abstract: Abstract. Emotional intelligence is a person's ability to know feelings and regulate their emotions in relation to other people, with emotional intelligence in employees, these employees will have a good work discipline attitude, where they will think and control their emotions before doing something, while up to Currently, it cannot be said that employees have good emotional management so that it will be difficult to create self-fitness for work or organization. Based on this phenomenon, the problems in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
0
0
4
Order By: Relevance
“…They do this to increase the interest of all employees, to feel satisfied with their respective jobs and the work in the organization where they work, so it can be concluded that emotional Intelligence can influence employee engagement in a company. This study's results follow research conducted by Susanti and Frendika (2021).…”
Section: Discussionsupporting
confidence: 86%
“…They do this to increase the interest of all employees, to feel satisfied with their respective jobs and the work in the organization where they work, so it can be concluded that emotional Intelligence can influence employee engagement in a company. This study's results follow research conducted by Susanti and Frendika (2021).…”
Section: Discussionsupporting
confidence: 86%
“…Pengelolaan pengetahuan yang baik dapat meningkatkan kemampuan karyawan untuk mengakses, menerapkan, dan berbagi pengetahuan mereka, sehingga memberikan kontribusi positif terhadap kinerja individu dan kelompok dalam mencapai tujuan organisasi. (Aldiassajjad & Sri Suwarsi, 2021;Hani Darmawati, 2021;Vini Tri Susanti & Rusman Frendika, 2022) Social capital mengacu pada jaringan sosial, hubungan interpersonal, dan kolaborasi antar individu di dalam organisasi. Knowledge management dapat memperkuat social capital dengan mendorong kolaborasi, pertukaran pengetahuan, dan pembelajaran kolektif.…”
Section: Aunclassified
“…Tentunya terdapat beberapa faktor yang dapat mempengaruhi turnover intention seperti lingkungan kerja dan beban kerja. (Manajemen et al, n.d.;Vini Tri Susanti & Rusman Frendika, 2022) Lingkungan kerja adalah segala sesuatu yang ada disekitar para pekerja yang dapat mempengaruhi pekerja dalam menjalankan tugas-tugas yang dibebankan (Nitisemito, 2020). Terdapat 2 dimensi dalam lingkungan kerja, pertama lingkungan kerja fisik yang terdapat disekitar tempat kerja dan dapat mempengaruhi karyawan dalam bentuk fisik.…”
Section: Aunclassified